Non-coding somatic mutations converge on the PAX8 pathway in ovarian cancer - Rosario I. Corona (Nature Portfolio, 2020)
The role of non-coding somatic mutations in ovarian cancer is unclear. Here, the authors integrate genomic and epigenomic data from patient samples to show that these mutations frequently converge on the PAX8 transcriptional network.